KEBIJAKAN PEMERINTAH KABUPATEN SIAK TERHADAP PEMBERDAYAAN PEREMPUAN SEBAGAI PEMOTONG GETAH KARET (KAJIAN DI KAMPUNG TELUK MEREMPAN KECAMATAN MEMPURA KABUPATEN SIAK) - Dessy Artina; Mexsasai Indra; Muhammad A. Rauf; Nur Ainun (Faculty of Law, Universitas Pattimura, 2021)
Indonesia is a constitutional state as stated in Article 1 Paragraph 3 of the 1945 Constitution and adheres to the concept of the rule of law. Indonesia is a democratic country that upholds the values of justice. Siak Regency is one of the districts in Riau Province which is synonymous with Malay culture. The values of local wisdom are still very thick in the life of the Malay people in Siak. The constitutional rights of citizens are regulated in the 1945 Constitution. In relation to fighting for constitutional rights, it cannot be denied that gender issues are an inhibiting factor for the development of society, especially for women. This is also an implication of the lack of system support that accommodates women in honing their potential and creativity, especially in rural areas. Therefore this paper is present as an emotional outpouring of questioning the role and involvement of women in the Merempan Hilir area to improve quality. family life through the agricultural sector built on the basis of rational arguments. The agricultural sector is the main sector that gets great attention and hope in rural communities and this agricultural sector is the main sector of livelihood for the people of the area. this is based on the characteristics of Indonesia as an archipelagic country which incidentally has an agrarian style, so that agricultural activities have become a tradition that is still well preserved today. However, the problem in the life of rural communities in general is the limited access to potential sources in an area. The type of research used is sociological legal research. This paper is the result of research made in the form of a final report and writing in this journal.